The Influence of Leadership Style, Work Discipline and Compensation on Employee Performance in the Regional Government of Ogan Komering Ilir Regency - Dany Supraja; Helmi, Sulaiman; Heriyanto; Darwin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to examine and analyze the influence of leadership style, work discipline and compensation on employee performance at the Regional Government Personnel, Education and Training Agency of Ogan Komering Ilir Regency. This research uses field research methods to study the background of the current situation and the social interactions within it. The research object was carried out in this environment by taking 45 employees as samples. Data collection was carried out through questionnaires using a Likert scale for quantitative analysis. The analysis techniques used include validity tests, reliability tests, and multiple linear regression analysis. To test the hypothesis, this research uses the F test, Coefficient of Determination test, and T test. The research results show that leadership style and work discipline do not have a significant influence on employee performance, while compensation has a positive and significant influence. This research suggests that future research can expand literature or articles as a reference to facilitate research, as well as adding other variables that have the potential to influence employee performance. It is also hoped that future research will use more holistic methods and integrate quantitative and qualitative approaches to gain a deeper understanding of the complexity of organizational dynamics. Thus, future research is expected to provide more comprehensive and relevant insights for the development of effective human resource management strategies in complex and dynamic work environments.